Dietary inflammatory index score, glucose control and cardiovascular risk factors profile in people with type 2 diabetes. (19th May 2021) - Vitale, Marilena; Calabrese, Ilaria; Massimino, Elena; Shivappa, Nitin; Hebert, James R.; Auciello, Stefania; Grioni, Sara; Krogh, Vittorio; Sartore, Giovanni; Signorini, Stefano; Rivellese, Angela A.; Riccardi, Gabriele; et al.
Abstract: We examined the relationships between the dietary inflammatory index (DII ® ), dietary habits and cardiovascular risk factor profiles in people with type 2 diabetes mellitus (T2DM). Energy-adjusted DII (E-DII™) scores were calculated from a Food Frequency Questionnaire in 2568 T2DM patients from different parts of Italy. Analyses were conducted according to quartiles of sex-specific E-DII scores. Higher, more pro-inflammatory, (quartile 4) E-DII scores were associated with overall poor quality of the diet characterised by higher content of refined carbohydrates, added sugars, saturated fat and cholesterol and lower unsaturated fat, fibre and polyphenols compared to quartile 1. Higher E-DII scores also were associated with higher waist circumference (105.4 vs. 103.5 cm; p  = 0.002), triglycerides (154.6 vs. 146.1 mg/dL; p  = 0.005), diastolic blood pressure (80.05 vs. 78.6 mmHg; p  = 0.04) and lower HDL-cholesterol (45.3 vs. 47.4 mg/dL; p  = 0.04). In conclusion, E-DII is a potent marker of overall quality of the diet and is associated with an unfavourable cardiovascular risk factor profile.